Atriplex Atacamensis and Atriplex Halimus Resist as Contamination in Pre-Andean Soils (Northern Chile) - Diaz-Schulze, O; Zuniga-Navarro, G; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Segura-Segura, R; Segura-Segura, R (2013)
The Pre-Andean area of Chile exhibits saline soils of volcanic origin naturally contaminated with arsenic (As), and we hypothesise that revegetation with resistant species may be a valid alternative for soil management in this area. Thus, the xerophytic and halophytic shrubs Atriplex halimus and Atriplex atacamensis were cultivated in containers for 90days in Pre-Andean soil, As-soil, (111±19mgAskg-1, pH8.4±0.1) or control soil (12.7±1.1mgAskg-1, pH7.8±0.1) to evaluate As accumulation and resistance using stress bioindicators (chlorophylls, malondialdehyde (MDA) and total thiols). Sequential extraction of As-soil indicated that 52.3% of As was found in the most available fraction. The As distribution was significantly different between the species: A. halimus translocated the As to leaves, whilst A. atacamensis retained the As in roots. At 30 and 90days, A. halimus showed similar As concentrations in the leaves (approximately 5.5mgAskg-1), and As increased in stems and roots (up to 4.73 and 16.3mgAskg-1, respectively). In A. atacamensis, As concentration was lower (2.6 in leaves; 3.2 in stems and 6.9 in roots in mgAskg-1). Both species exhibited a high concentration of B in leaves (362-389mgkg-1). If the plants are used for animal feed, it should be considered that A. halimus accumulates higher concentration of As and B in the leaves than A. atacamensis. Neither plant growth nor stress bioindicators were negatively affected by the high levels of available As, with the exception of MDA in the leaves of A. halimus. The results indicate that these plants resist contamination by arsenic, accumulating mainly the metalloid in the roots and can be recommended to generate plant cover in As-contaminated soils in the Pre-Andean region, under saline conditions controlled, preventing the dispersion of this metalloid via wind and leaching. © 2013 Elsevier B.V.